2016
DOI: 10.3389/fnhum.2016.00516
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala fMRI Signal as a Predictor of Reaction Time

Abstract: Reaction times (RTs) are a valuable measure for assessing cognitive processes. However, RTs are susceptible to confounds and therefore variable. Exposure to threat, for example, speeds up or slows down responses. Distinct task types to some extent account for differential effects of threat on RTs. But also do inter-individual differences like trait anxiety. In this functional magnetic resonance imaging (fMRI) study, we investigated whether activation within the amygdala, a brain region closely linked to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 114 publications
(142 reference statements)
0
6
0
Order By: Relevance
“…Details of the recruitment, screening, and objectives of this study can be found in Marxen et al (2016). On Experimental Day 1, a T1-weighted MRI, a resting state fMRI sequence, the ACES task, and a further task (Riedel et al, 2016) were acquired. We will focus here on the ACES task (see below for details).…”
Section: Experimental Designmentioning
confidence: 99%
“…Details of the recruitment, screening, and objectives of this study can be found in Marxen et al (2016). On Experimental Day 1, a T1-weighted MRI, a resting state fMRI sequence, the ACES task, and a further task (Riedel et al, 2016) were acquired. We will focus here on the ACES task (see below for details).…”
Section: Experimental Designmentioning
confidence: 99%
“…Whilst reaction time tasks are regarded a reliable and valuable measure for cognitive responses, the threat of attention loss and variability in speed between participants threatens its validity (Riedel et al, 2016). Additionally, the risk of habituation and associated attenuation of BOLD response remains.…”
Section: Discussionmentioning
confidence: 99%
“…As reaction time tests have the potential to reveal inter-individual differences in e.g. anxiety (Riedel et al, 2016) which could in turn influence BOLD response or slow reaction times (Ford et al, 2018), we assessed state anxiety pre and post scan for both protocols. There was no change in state anxiety, suggesting that the change in reaction times should not be attributed to feelings of participant apprehension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Riedel P et al states that reaction times are a valuable measure for assessing cognitive processes [47].…”
Section: Reaction Timementioning
confidence: 99%